1996
DOI: 10.1172/jci118849
|View full text |Cite
|
Sign up to set email alerts
|

Diminished post-rest potentiation of contractile force in human dilated cardiomyopathy. Functional evidence for alterations in intracellular Ca2+ handling.

Abstract: Post-rest contractile behavior of isolated myocardium indicates the capacity of the sarcoplasmic reticulum (SR) to store and release Ca 2 ϩ . We investigated post-rest behavior in isolated muscle strips from nonfailing (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
124
0
10

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(148 citation statements)
references
References 65 publications
14
124
0
10
Order By: Relevance
“…Second, and less well understood, is that the processes underlying frequency dependent behavior are geared to provide an increase in contractility, and thus may impact on the temporal resolution via which PRP is achieved. Further evidence in that PRP and FFR are closely linked is found in the studies on failing myocardium, where both PRP [53] and FFR [3,54] seem to be blunted and hallmarks of the contractile phenotype of failing myocardium.…”
Section: Post-rest Potentiation and Extra-systolic Behaviormentioning
confidence: 91%
“…Second, and less well understood, is that the processes underlying frequency dependent behavior are geared to provide an increase in contractility, and thus may impact on the temporal resolution via which PRP is achieved. Further evidence in that PRP and FFR are closely linked is found in the studies on failing myocardium, where both PRP [53] and FFR [3,54] seem to be blunted and hallmarks of the contractile phenotype of failing myocardium.…”
Section: Post-rest Potentiation and Extra-systolic Behaviormentioning
confidence: 91%
“…The active properties of the failing non-infarcted tissue were scaled from human data (Pieske et al, 1996), in which peak myofiber stress was 27% lower than in healthy tissue, and relaxation prolonged by 17%.…”
Section: Mechanical Materials Propertiesmentioning
confidence: 99%
“…However, the same authors have reported that cardiomyocytes derived from iPSC exhibited negative force-frequency relationship and lower postrest potentiation than adult cardiac cells [71]. The force-frequency relationship is termed 'positive' when contractility increases as stimulation frequencies are stepped up and 'negative' when increased frequency of stimulation is associated with reduced contraction force [72,73]. Impaired force-frequency relationship is one of the hallmarks of the failing heart [73][74][75].…”
Section: Cardiomyocytes Derived By Differentiation Of Esc and Ipscmentioning
confidence: 99%
“…The force-frequency relationship is termed 'positive' when contractility increases as stimulation frequencies are stepped up and 'negative' when increased frequency of stimulation is associated with reduced contraction force [72,73]. Impaired force-frequency relationship is one of the hallmarks of the failing heart [73][74][75]. Post-rest contractile behaviour of myocardium is an indicator for the capacity of the sarcoplasmic reticulum for storage and release of Ca 2+ .…”
Section: Cardiomyocytes Derived By Differentiation Of Esc and Ipscmentioning
confidence: 99%